Serving Others: Keteladanan Pelayanan Yesus Kristus Berdasarkan Yohanes 13 - Giawa, Nasokhili (Sekolah Tinggi Teologi Jaffray Jakarta, 2019)
To serve is a terminology that is often found in relation with the tasks and responsibilities that are being carried out. This word is an important word that has recently become a jargon used more often by leaders in Indonesia, especially in the context of leadership implementation. Indeed, this is the core of the call that Jesus Christ had taught. However, this term has been reduced to a kind of ordinary terminology without getting any deep meaning. From a Christian perspective (church), to serve is a popular language to translate and to be implemented especially because Jesus Christ taught his disciples and also to His followers. Therefore, when discussing about church affairs it is closely related to how to serve. In addition, to being taught through the Gospel of John and through Mark's Gospel, we learn about the depth of the meaning of service by placing Jesus Christ as Servant - who humbled Himself in order to serve.